Spremembe in dopolnitve Zakona o rudarstvu in mednarodni vidiki posrednih razlastitev - Tomažič, Luka Martin (Podjetje in delo, 2022)
With the amendment to the Mining Act (ZRud-1), the legislator altogether banned hydraulic fracturing technology under the precautionary principle and considered the possible negative consequences for the environment. This article analyses aspects of international human rights and investment law, particularly Slovenia's obligations under the European Convention on Human Rights and Fundamental Freedoms and the Energy Charter Treaty. Criteria have been researched and critically discussed, the fulfilment of which could lead to indirect expropriations in individual cases. In related cases, the European Court of Human Rights generally decides that countries have a wide margin of appreciation concerning legislative activity relating to environmental protection. In this context, the finding of infringements is less likely. The Energy Charter Treaty is vaguer, which seems to allow enough room for interpretation that in individual cases, if the relevant criteria are met, there are illegal indirect expropriations. According to the case law of the Court of Justice of the European Union, the applicability of the Energy Charter Treaty is excluded for relations between investors from the EU Member States and European Union Member States that are also parties to the Energy Charter Treaty.
Keywords: ECtHR; Energy Charter Treaty; ESČP; fracking; hidravlično lomljenje; hydraulic fracturing; mining; nacionalizacija; nationalisation; natural gas; Pogodba o energetski listini; rudarstvo; zemeljski plin